Avaliação da gestão de projetos de inovação no Instituto Federal de Educação, Ciência e Tecnologia do Sul de Minas Gerais - IFSULDEMINAS - Novaes, Paulo Henrique (2019)
This dissertation addresses the results of research focused on innovation projects managed by a scientific technological institution (ICT) in the context of program and project management. The theoretical framework is based on the PMBOK guide (6th ed.), The Standard for Program Management (SPM), both developed by the Project Management Institute (PMI) and the Model Practical NCTP "Diamond" (Shenhar et al., 2005). Among the various public ICTs that promote innovation, the Federal Institutes of Education, Science and Technology emerge in a regional environment. The objective of the research was to evaluate the management of the program and its innovation projects to improve the performance of IFSULDEMINAS in fulfilling its strategic mission to promote innovation in its territorial environment. Research is defined as predominantly qualitative, exploratory-descriptive, delineated as a single case study. The analysis of the public and private documents allowed to describe the profile of the innovation projects and to compare the management of the Institutional Program of Incentive to the Development of Technological Innovation (PIIDIT) with the PMI-SPM standard. The data collected by questionnaire allowed to evaluate the final maturity (AFM), adherence to the levels and dimensions of maturity of the project managers and the management of PIIDIT, according to model Prado-MMGP Sector. Regarding the comparison between PIIDIT management and PMI-SPM program management standard, the results demonstrated that quality and risk program activities, such as program activity management plans, need to be created and executed. In addition, it demonstrated that the lack of a specific computer program and a project management office or a human resources adequacy in the NTI/IFSULDEMINAS, become critical points for future pretensions. The profile of the innovation projects completed in PIIDIT points out congruent characteristics related to innovative projects, in addition the data obtained through the AFM, adherence to the levels and dimensions of maturity allowed to conclude that both innovation project managers and management of PIIDIT are at level 2 (known) of maturity, but with a maturity level to other brazilian references and with the potential to evolve from a growth plan in maturity in management.